STUDI KOMPETENSI PEDAGOGIK GURU DI TAMAN KANAK-KANAK KECAMATAN PONTIANAK BARAT - Hastuti, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractTeachers are an educator to plan,carry out a process and evaluate learning to produce outputs pendidiikan quality. So as to have performance was good and produce outputs quality education requiring teachers to have competency standard of them competence pedagogical.A problem common in this research is how competence pedagogical teacher at kindergarten sub-district Pontianak west ? A Special matter in this research was (A)How the results of value competency test of pedagogical teacher at kindergarten sub-district Pontianak west? B)Whether obstacles kindergarten teachers sub-district Pontianak west in mastering competence pedagogical?(C)How efforts teachers in improve the competence of pedagogical teacher at kindergarten sub-district Pontianak west ?A common purpose this study is to find competence pedagogical teacher at kindergarten sub-district Pontianak west.The subject of study: 54 people kindergarten teachers sub-district Pontianak west who have followed test competence the form of this research is research quantitative .Methods used deskriptif-kuantitatif .Research results show that the 1 of the results of the value of competency test pedagogical teacher at kindergarten sub-district Pontianak west most in the category of being with intervals 50-59 value as many as 23 people teacher or 34.3 %, (2)Obstacles kindergarten teachers sub-district Pontianak west in mastering pedagogical namely competence; A)The internal factor 1)Tenure and work experience, 2)Welfare, b)External factors (1)Large salary and received allowance, (2)Maintenance activity done. (3)Teacher efforts to improve the competence of pedagogical teacher at the park childhood in Pontianak west; a)The efforts made at school level in; 1)Efforts made by sending teachers to undertake training, upgrading courses, workshops and seminars,2)Training exercises computer and english language (b)Efforts at school level in; 1)Make the planning scheduled to the development of potential 2)Do assessment to improve and or quality of learning in class.Â Keywords: Competency Standard, Pedagogical Competence